Role of laparoscopy in the Etiologic Diagnosis of Ascites of Unknown Origin - Sharma, Anup; Thapa, P.; Gupta, S. N. (Journal of Nepalgunj Medical College, 2017)
Introduction: Ascites is a consequence of many different etiologies, such as liver cirrhosis, neoplasm, tuberculous peritonitis, pyogenic peritonitis, congestive heart failure, renal and pancreatic diseases but, in some situations, ascites is of unknown cause in spite of comprehensive study. The aim of this study was to identify the role of laparoscopy in the etiological diagnosis of ascites of unknown origin. Methods: This was a prospective study of the patients who underwent diagnostic laparoscopy to determine the causes of ascites of unknown origin in the Department of Surgery, Nepalgunj Medical College Teaching Hospital from April 2012 to May 2014. All the patients underwent laparoscopy for the evaluation of ascites after appropriate clinical and laboratory examinations, which failed to reveal the cause. Results: Peritoneal tuberculosis and carcinomatosis peritonei were the two most common causes found in 37.14% and 57.14% of cases respectively. The average age of the patients was 52 years. Distension of abdomen, abdominal pain and weight loss were the most frequently observed symptoms in 33 patients (100%), 26 patients (74.28%) and 18 patients (51.42%) respectively. The CT scan findings, were a omental thickening in 28 cases (80%), peritoneal nodules in 7(20%) patients and the intraabdominal lymph nodes in 13 patients (39.39%). Ovarian mass was found in 4 patients (11.42%). The histological diagnosis was a peritoneal carcinomatosis in 13 (37.14%) patients and peritoneal tuberculosis in 20 (57.1%) patients and in two patients nonspecific inflammation. The sensitivity and specificity of laparoscopic diagnosis in the diagnosis of peritoneal tuberculosis were 78.67% and 98.6% respectively and in the diagnosis of peritoneal carcinomatosis were 94.78% and 72.2% respectively. The positive predictive value was 97.3% and the negative predictive value was 73.7% for peritoneal tuberculosis and for peritoneal carcinomatosis the positive predictive value was 83.7% and negative predictive value was 94.87%. Conclusion: The etiologic diagnosis of ascites of unknown origin is difficult despite the availability of several tests. Laparoscopy with peritoneal biopsy has still got a role in diagnosing these types of ascites where the other laboratory and imaging studies fail to reveal the cause. Journal of Nepalgunj Medical College Vol.13(1) 2015: 13-16